PHYTOCHEMICAL PROFILING, HPTLC FINGERPRINT AND ANTIBACTERIAL, ANTI-FUNGAL, AND ANTIOXIDANT PROPERTIES OF ESSENTIAL OILS EXTRACTED FROM CUMMINUM CYMINUM, ZINGIBER OFFICINALE, TRACHYSPERMUM AMMI, ALIPNIA GALANGA, CEDRUS DEODARA, AND ELETTARIA CARDAMOMUM - P, GURUVAURAPPAN; SAHOO, MANAS RANJAN; VARIER, RAMESH RAGHAVA; RAJENDRAN, ANITHAKUMARI; HAREKRIHSN, MAHESWARI; KARUPPASAMY, RAMESH; S, SRIKRISHNA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the study was to carry out the phytochemical profiling of essential oils (EOs) and evaluation of their anti-microbial activity. Methods: The EOs extracted from Cumminum cyminum, Zingiber officinale, Trachyspermum ammi, Alipnia galanga, Cedrus deodara, and Elettaria cardamomum using clavenger apparatus. Phytochemical analysis and high-performance thin layer chromatography (HPTLC) fingerprinting were carried out for the EO. The antibacterial and antifungal activity were evaluated using agar well-diffusion method against two bacterial strains, Escherichia coli, Staphylococcus aureus and two fungal strains, Candida albicans, and Aspergillus brasiliensis. Positive controls ciprofloxacin-30 mg, azithromycin-15 mg, and nystatin NS-50 mg were used. Antioxidant potential of the EOs was investigated by TLC-bioautography method using 1,1-diphenyl-2-picrylhydrazyl derivatization. Results: The phytochemical analysis reveals presence of various phytochemical such as steroids, terpenoids, and phenylpropanoids. The HPTLC fingerprint is found to be unique for each of the oil. The EO of Z. officinale and T. ammi showed strong antibacterial activity against S. aureus. The EOs of C. cyminum, Tachyspermum ommi and A. galanga displayed prominent antioxidant activity on TLC bioautography. The herbs Cuminum cynimun, T. ammi, C. deodara, and Ellateria cardamomum produce reasonable amount of essentials oil, which can be explored for useful their industrial applications. Conclusions: These EOs can be explored further for their antimicrobial activity. The HPTLC analysis along with derivatization with suitable chromogenic reagents can be a rapid and simple tool for quality control of various EOs.